Impact of Pre-Therapy Viral Load on Virological Response to Modern First-Line Haart. Issue 7 (October 2013) - Santoro, Maria Mercedes; Armenia, Daniele; Alteri, Claudia; Flandre, Philippe; Calcagno, Andrea; Santoro, Mario; Gori, Caterina; Fabeni, Lavinia; Bellagamba, Rita; Borghi, Vanni; Forbici, Federica; Latini, Alessandra; et al.
Background: We tested whether pre-HAART viraemia affects the achievement and maintenance of virological success in HIV-1-infected patients starting modern first-line therapies. Methods: A total of 1, 430 patients starting their first HAART (genotype-tailored) in 2008 (median; IQR: 2006–2009) were grouped according to levels of pre-HAART viraemia (≤30, 000, 30, 001–100, 000, 100, 001–300, 000, 300, 001–500, 000 and >500, 000 copies/ml). The impact of pre-therapy viraemia on the time to virological success (viraemia ≤50 copies/ml) and on the time to virological rebound (first of two consecutive viraemia values >50 copies/ml after virological success) were evaluated by Kaplan–Meier curves and Cox regression analyses. Results: Median pre-HAART viraemia was 5.1 log10 copies/ml (IQR 4.5–5.5), and 53% of patients had viraemia >100, 000 copies/ml. By week 48, the prevalence of patients reaching virological success was >90% in all pre-HAART viraemia ranges, with the only exception of range >500, 000 copies/ml (virological success =83%; P <0.001). Higher pre-HAART viraemia was tightly correlated with longer median time to achieve virological success. Cox multivariable estimates confirmed this result: patients with pre-HAART viraemia >500, 000 copies/ml showed the lowest hazard of virological undetectability after adjusting for age, gender, pre-HAART CD4 + T-cell count, transmitted drug resistance, calendar year and third drug administered (adjusted hazard ratio [95% CI]: 0.27 [0.21, 0.35]; P <0.001). Pre-HAART viraemia >500, 000 copies/ml was also associated with higher probability of virological rebound compared with patients belonging to lower viraemia strata at weeks 4, 12 and 24 ( P =0.050). Conclusions: At the time of modern HAART, and even though an average >90% of virological success, high pre-HAART viraemia remains an independent factor associated with delayed and decreased virological success. Patients starting HAART with >500, 000 copies/ml represent a significant population that may deserve special attention.